The UTILIZATION OF APPRAISAL SYSTEM FOR COPYWRITING STRATEGY IN FOOD’S ADVERTISEMENT (A SYSTEMIC FUNCTIONAL LINGUISTIC APPROACH) - Rahmaditya Khadifa Abdul Rozzaq Wijaya; Syafrianto Syafrianto; Muhammad Zidan Akbar (Proceeding of International Conference on Science, Health, And Technology, 2022)
This paper investigated the appraisal system used in the copywriting of food advertisements. The purpose of this research was to describe the utilization appraisal system in food advertisements. This study is qualitative and descriptive research. The data gathered from emotive words that contain about attitudes (affect, judgment, and appreciation) in the caption and picture of food advertisements. The instagram account of burgerking, pizzahut, and richeese factory as the data source. The result is the implementation of affect, appreciation, and judgment for copywriting strategy of the advertisement.